2002
DOI: 10.1016/s0735-1097(01)01826-5
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant N-2-mercaptopropionyl glycine attenuates left ventricular hypertrophy in in vivo murine pressure-overload model

Abstract: Our results indicated that oxidative stress was increased in our model and that it plays an important role in the development of cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 19 publications
6
103
1
3
Order By: Relevance
“…9 In an in vivo murine model of pressure overload, we were able to show that pressure overload-induced oxidative stress in hearts and the resultant cardiac hypertrophy were attenuated by treatment with the antioxidant mercaptopropinonyl glycine. 11 However, for clinical use, an antioxidant with high accessibility to tissue or relatively slow clearance is needed. Edaravone was proven to have an inhibitory effect on a water-soluble and a lipid-soluble peroxyl radical-induced peroxidation system and to have sufficient accessibility to tissue, including hearts, so that it can effectively scavenge ROS in heart.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In an in vivo murine model of pressure overload, we were able to show that pressure overload-induced oxidative stress in hearts and the resultant cardiac hypertrophy were attenuated by treatment with the antioxidant mercaptopropinonyl glycine. 11 However, for clinical use, an antioxidant with high accessibility to tissue or relatively slow clearance is needed. Edaravone was proven to have an inhibitory effect on a water-soluble and a lipid-soluble peroxyl radical-induced peroxidation system and to have sufficient accessibility to tissue, including hearts, so that it can effectively scavenge ROS in heart.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Similar results have been obtained with in vivo study. 11 Apoptosis signal-regulating kinase 1 (ASK1) is an ROSsensitive mitogen-activated protein (MAP) kinase kinase kinase that activates the c-Jun N-terminal protein kinase (JNK) and p38 MAP kinase. 12 ASK1 is associated with thioredoxin as an inactive form in nonstressed cells.…”
mentioning
confidence: 99%
“…Previous reports demonstrated that antioxidants attenuate pressure-overload cardiac hypertrophy. 19 Transgenic cardiac overexpression of thioredoxin decreases the myocardial infarct size after ischemia/reperfusion injury 20 and protects against adriamycininduced cardiotoxicity by reducing oxidative stress. 21 Therefore, thioredoxin may play a pivotal role in the myocardial defense against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…32 Our finding that pressure overload-induced nitrotyrosine staining is markedly inhibited by EPL implicates mineralocorticoid receptors in mediating at least some of the increased oxidative stress that has been appreciated in myocardium subjected to pressure overload. 43 The mechanism by which mineralocorticoid receptors mediate oxidative stress remains to be determined. However, Sun et al 12 observed that inhibition of NADPH oxidase ameliorates the adverse myocardial effects of aldosterone, suggesting that NADPH oxidase may be a source of reactive oxygen species in response to mineralocorticoid receptors activation.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%